A highly selective chromogenic probe for the detection of nitrite in food samples. (1st July 2020) - Chen, Yinyin; Zhao, Chenxi; Yue, Guizhou; Yang, Zhouping; Wang, Yanying; Rao, Hanbing; Zhang, Wei; Jin, Bo; Wang, Xianxiang
Highlights: The simple and convenient method for detection of nitrite is developed. The nitrite concentration can be detected quickly and conveniently by the naked eye. A linear detection range for nitrite is 1–75 μM and the LOD is 0.73 μM for nitrite ions. Abstract: A rapid, sensitive, and highly selective method for determining nitrite in food has been developed. This method is based on the reaction of nitrite with the amino group of 3, 3, 5, 5-tetramethylbenzidine (TMB) to form a diazonium salt, and then the diazonium salt and glucosamine hydrochloride are coupled to each other to form an orange compound. The optimal conditions for maximum color and other analytical parameters were studied. A colorimetric method for nitrite detection has been developed with an outstanding correlation coefficient (R 2  = 0.9944), a wide linear range (1–75 μM) and 0.73 μM limit of detection (at S/N = 3) for nitrite ions. This method was successfully applied to the determination of nitrite in a variety of foods and gave recoveries in the range between 100.16% and 103.07%, demonstrating that the accuracy, reliability and potential application of this assay for monitoring nitrite in foods.